If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.2(x + 3) + -3(2x + 4) = 8 + -6x Reorder the terms: 0.2(3 + x) + -3(2x + 4) = 8 + -6x (3 * 0.2 + x * 0.2) + -3(2x + 4) = 8 + -6x (0.6 + 0.2x) + -3(2x + 4) = 8 + -6x Reorder the terms: 0.6 + 0.2x + -3(4 + 2x) = 8 + -6x 0.6 + 0.2x + (4 * -3 + 2x * -3) = 8 + -6x 0.6 + 0.2x + (-12 + -6x) = 8 + -6x Reorder the terms: 0.6 + -12 + 0.2x + -6x = 8 + -6x Combine like terms: 0.6 + -12 = -11.4 -11.4 + 0.2x + -6x = 8 + -6x Combine like terms: 0.2x + -6x = -5.8x -11.4 + -5.8x = 8 + -6x Solving -11.4 + -5.8x = 8 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -11.4 + -5.8x + 6x = 8 + -6x + 6x Combine like terms: -5.8x + 6x = 0.2x -11.4 + 0.2x = 8 + -6x + 6x Combine like terms: -6x + 6x = 0 -11.4 + 0.2x = 8 + 0 -11.4 + 0.2x = 8 Add '11.4' to each side of the equation. -11.4 + 11.4 + 0.2x = 8 + 11.4 Combine like terms: -11.4 + 11.4 = 0.0 0.0 + 0.2x = 8 + 11.4 0.2x = 8 + 11.4 Combine like terms: 8 + 11.4 = 19.4 0.2x = 19.4 Divide each side by '0.2'. x = 97 Simplifying x = 97
| 4x-14(1-7)=-626 | | a/2+1/5=17 | | 120=50t-5t^2 | | [10x-9]+3=14 | | 1(6y-1)=1y | | 3(x+8)+x=32 | | 6a-3=4a+3 | | -6+8(8n-5)=274 | | -3/10=x/10 | | a-6a=0 | | (11x+8)(11x-8)=121x-64 | | 2x-6(x-1)=6-(4x+6) | | -6(-5x+6)=144 | | x+2+x+1=x+7+x+9+x+3 | | x+2=4(x-3) | | 5.2t+14.6-10.1t=12.8-3.5t-0.6 | | (5-11i)(5+11i)= | | 4n+2-1=9 | | 4x^4= | | 4b+3+3b=43-3b | | -5(-14+4n)=330 | | 5x-2(3x-2)=-2x+6 | | a/2+1/2=17 | | 2x+5+3x=14-2x-2 | | -4y-(2y+5)=1(7+8y) | | 6x+30=x+50 | | 2(5w-3)+25=3(4w+1) | | 4x^2-8x+21=0 | | -x+15+9x-12+7(-3x-10)=3x-x+11-5(2x+7)-78 | | 8=1+2k+5 | | 2x+16+x+14=180 | | 2z+9.75-7z=-5.25 |